2019
DOI: 10.1093/bjsw/bcz103
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Staying: A Longitudinal Study of Work Conditions Predicting Social Workers’ Willingness to Stay in Their Organisation

Abstract: Extensive staff turnover within the statutory social services is a serious problem in Sweden and in other European countries. This study examines which work conditions predict social workers’ willingness to stay in their organisation. A web-based questionnaire was used to gather data. The participating social workers responded to two questionnaires over a one-year period. To identify the social workers who wanted to stay and also remained in the organisation, the group ‘Stayers’ (n = 1,368) consisted of social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…The result agrees with numerous previous studies which indicated that intra-role conflict has negative impacts on the intention to stay in the organization (Awan, et al, 2021;Worku, 2015). Astvik et al (2020) explained that when the demands of performing two tasks compete against each other, the employee will find it difficult to know which type of tasks to perform which leads to the intention to stay in the organization. According to the spillover theory (Berry et al, 1992), the intention to stay in an organization is a function of job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The result agrees with numerous previous studies which indicated that intra-role conflict has negative impacts on the intention to stay in the organization (Awan, et al, 2021;Worku, 2015). Astvik et al (2020) explained that when the demands of performing two tasks compete against each other, the employee will find it difficult to know which type of tasks to perform which leads to the intention to stay in the organization. According to the spillover theory (Berry et al, 1992), the intention to stay in an organization is a function of job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…It indicates the willingness of employees to remain on the job in a foreseeable future. The employees are usually aware of their intentions after a cautious reflection (Astvik et al, 2020). The tendency to stay on the job demonstrates employees' interests and willingness to help the organization to achieve its goals and objectives (You-De et al, 2019).…”
Section: Literature Review Intention To Stay On the Jobmentioning
confidence: 99%
See 1 more Smart Citation
“…Job resources refer to those physical, psychological, social, or organisational aspects of the job that are functional in achieving work goals, reduce job demands and the associated physiological and psychological costs, or stimulate personal growth, learning, and development (e.g., social support, performance feedback, autonomy, opportunities for development, degree of participation in decision making) [26,60]. In the case of social workers, the most relevant job resources which can buffer against the negative effects of demands are: the rewarding nature of the role, peer support and management support [61], human resource orientation, and openness as dimensions of the psychological climate [62].…”
Section: Job Demands-resources Theorymentioning
confidence: 99%
“…Awareness of uncertainty, ongoing critical thinking, and constant negotiations are critical skills for approaching uncertainties [20]. The managerial challenge and responsibility is to create sustainable work conditions that facilitate a stable workforce and the provision of good social services [62]. Transformational leadership [63] is required in social services to embrace the challenges of the new era if social work should not come to an end [80].…”
mentioning
confidence: 99%